Sistem Penunjang Keputusan Dengan Metode AHP dan WASPAS Untuk Penentuan Penerima Bantuan Pangan Non Tunai (BPNT) - Rita; Guslendra (Riset Sinergi Indonesia (RISINDO), 2025)
BPNT (Non-Cash Food Assistance) is a government program aimed at reducing the financial burden of poor families by providing non-cash food assistance, as well as improving food security and the welfare of vulnerable and impoverished communities in Indonesia. The process of determining BPNT recipients is conducted conventionally, which often results in errors that lead to complaints from the public, as well as challenges in data collection and verification, reducing the accuracy of BPNT distribution. The aim of this research is to enhance the efficiency, transparency, and accuracy of the process for determining BPNT recipients in Padang City. The method used in this research is a combination of Analytical Hierarchy Process (AHP) and Weight Aggregated Sum Product Assessment (WASPAS) to generate systematic, objective decisions and reduce subjective bias in the selection process of potential beneficiaries. The data for this research were obtained through field surveys, collecting assessments related to employment, income, housing conditions, age, and the number of dependents of the respondents. The results of the research indicate that through ranking, the application of the combination of Analytical Hierarchy Process (AHP) and Weight Aggregated Sum Product Assessment (WASPAS) is effective in simplifying the evaluation and decision-making process, as well as identifying families who are ineligible to receive BPNT. This structured and well-documented assessment process supports the improvement of BPNT distribution effectiveness and enhances services to communities in need.